Adoption of Audit Management System within Audit farms in Bangladesh - Mahbuba Husnat Medha; Mehzabul Hoque Nahid; Mahreen Naadia (Indonesia Auditing Research Journal, 2023)
This study aims to understand the challenges of adopting an audit management system in Bangladesh from the perspectives of audit firms. These challenges are also mapped to different contexts within the technological-organizational-environmental (TOE) framework. The authors conducted 10 semi-structured interviews with managers in different audit firms in Bangladesh. The authors used a qualitative exploratory approach by applying coding and thematic analysis to arrive at findings and conclusions. The study's most important finding was the identification of environmental variables as a major driver of adoption. This research has uncovered previously unrecognized elements, such as the need for a professional and regulatory environment conducive to auditing and the value of having access to an Audit Management System in many languages. This research adds to the existing body of knowledge by, among other things, highlighting novel moderating elements of the Theory of Excellence (TOE) Framework. This approach goes beyond the typical auditing focus on the person to include the company and has seen little use in the academic literature. In addition, various audit businesses are analyzed from the vantage point of a developing nation. However, much of the research done so far is Western-centric and focuses on big auditing companies. Whereas earlier research focused on surveys, the semi-structured interviews used in this study allow for a more thorough investigation.